iThrust News Certificate: A Blockchain-Based Solution for News Verification and Reputation Management - Miljkovic, Aleksandar; Cabarkapa, Milan; Miljkovic, Filip; Bojic, Ljubisa (Journal of Computer and Forensic Sciences, 2023)
The proliferation of fake news and misinformation in the digital era poses a significant challenge to news organizations and content creators. In this paper, we introduce iThrust News Certificate, the architecture of an online blockchain-based solution designed to combat fake news, enhance news verification, and maintain reputation within the media ecosystem. Unlike previous attempts, iThrust News Certificate focuses on user-friendly features while ensuring transparency and reliability.
Keywords: fake news; blockchain; smart-contracts